Measurement of Inflammation-Related Biomarkers in Different Chronic Kidney Diseases in Humans: Role of Aging and Gender? - Ahmad, Abdulla; Ajeel, Mohammed; Aldabbagh, Karam (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Chronic kidney disease (CKD) is a worldwide health problem which becomes a substantial emerging cause of morbidity. The inflammation can be resulted via different mechanisms in different kidney diseases including the imbalance of proinflammatory/anti-inflammatory biomarkers levels. This study aimed to measure the level of physiological bioactive substances as inflammation-related biomarkers in different CKD and to investigate whether gender or aging is critical in these measurements. MATERIALS AND METHODS: 84 persons (19 healthy, 29 chronic glomerulonephritis, 26 diabetic nephropathy, 6 benign nephrosclerosis, 4 lupus nephritis) were enrolled in this study. The inflammation progression degree in CKD was estimated by measuring the plasma level of neutrophil gelatinase-associated lipocalin (NGAL), monocyte chemoattractant protein 1 (MCP1), and clusterin (CLU) using ELISA. Serum total protein, urea and creatinine were measured using an automatic analyzer. RESULTS: Plasma level of urea and creatinine was increased while total protein level was decreased in all the patients compared to control participants. The level of NGAL, MCP1 and CLU was significantly increased in all the kidney diseases compared to controls. In addition, there were no differences in the level of inflammation-related markers between women and men. Moreover, the levels of inflammatory markers were increased in the kidney diseases regardless of the age difference. CONCLUSIONS: This study showed that the physiological bioactive substances NGAL, MCP1 and CLU can be increased in renal pathologies and considered as good indicators of progression of inflammation in chronic kidney diseases, with no role of gender and age in their increment plasma levels.